2019
DOI: 10.1155/2019/8512405
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Mechanisms of Xinmailong Injection, a Periplaneta Americana Extract, on Cardiovascular Disease: A Systematic Review of Basic Researches

Abstract: Background. At present, the prevention and treatment of cardiovascular disease in the world are facing severe challenges. Xinmailong injection, which is derived from the animal medicine Periplaneta Americana, has certain advantages in the clinical treatment of cardiovascular disease. This study systematically evaluated the basic research reports of Xinmailong Injection on cardiovascular disease and made its pharmacological mechanisms more clear. Methods. Basic research reports on the intervention mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Kangfuxin Liquid and Xinmailong Injection are extracted from Periplaneta americana and are highly recognized for their efficacy in treating wound healing, kidney and cardiovascular disease, etc. 14 , 31 Interestingly, in our study, we found that PAE had inhibitory effects on the differentiation of osteoclasts, including inhibiting the formation of osteoclasts, down‐regulating the expression of osteoclast genes, and reducing the activity and function of osteoclasts, indicating its potential as an alternative strategy for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 62%
“…Kangfuxin Liquid and Xinmailong Injection are extracted from Periplaneta americana and are highly recognized for their efficacy in treating wound healing, kidney and cardiovascular disease, etc. 14 , 31 Interestingly, in our study, we found that PAE had inhibitory effects on the differentiation of osteoclasts, including inhibiting the formation of osteoclasts, down‐regulating the expression of osteoclast genes, and reducing the activity and function of osteoclasts, indicating its potential as an alternative strategy for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 62%
“…The TCMIs included in this study all have the effect of nourishing Qi and blood. And a large number of articles and reviews have explored the protective effects of the active ingredients of these TCMIs on cardiovascular diseases in terms of molecular mechanisms, such as Huang-Qi ( Radix Astragali ) ( Su et al, 2021 ) in HQ, the combination of Ren-Shen ( Radix Ginseng ) and Fu-Zi (processed) ( Radix Aconiti Lateralis Preparata ) ( Tan et al, 2018 ; Li L. et al, 2020 ) in SF, the combination of Hong-Shen ( Radix Ginseng Rubra ) and Mai-Dong ( Radix Ophiopogonis ) ( Wang et al, 2019 ) in SM and YQFM, Wu-Wei-Zi ( Fructus Schisandrae ) ( Nasser et al, 2020 ) in SGM, and American cockroach ( Periplaneta Americana Linnaeus ) ( Qi et al, 2017 ; Lin S. S. et al, 2019 ) in XML. Due to the available active ingredients, rich and diverse targets, and complex regulatory mechanisms, TCMIs have considerable development potential.…”
Section: Discussionmentioning
confidence: 99%
“…XMLI was prepared from the extract of the animal TCM Periplaneta americana. Periplaneta americana is a natural animal medicine that can eliminate inflammation and edema, promote wound healing, and improve immune function (Lin et al, 2019;Zeng et al, 2019;Liao et al, 2022;Pang et al, 2022). HJTI is prepared from an extract of the traditional Chinese medicine Rhodiolae Crenulatae Radix et Rhizoma.…”
Section: Single Tcm Extract Injectionmentioning
confidence: 99%